(untitled) (Kerala Journal of Psychiatry, 2022)
Background: The COVID 19 pandemic is associated with mental health concerns such as anxiety and depression at multiple levels and has recently been postulated to be linked to the long COVID syndrome. Objectives: To determine the prevalence and factors associated with depression and anxiety in individuals admitted with COVID-19 infection. Methods: 154 individuals admitted with COVID-19 infection were screened for depression and anxiety employing PHQ9 and GAD 7, respectively. Trained interns did the screening on consecutively admitted patients. Results: The proportion of depression and anxiety was 26.6%(n=41) and 20.1%(n=31), respectively. Moderate and above symptoms were present in 3.9% of the individuals(n=6) on both scales. Older age (t=2.124, p=.035), lower educational status (t=3.725, p=0.000), a family member losing their job during the pandemic (t=1.91, p=0.05), presence of fever (t=2.069, p=0.040), oxygen therapy (t=2.19, p=0.030) and treatment with hydroxychloroquine (t=2.122, p=0.035) were found to be significantly associated with high depression scores. Being less educated (t=3.594,p=0.000), admission under non-paying status (t=2.209, p=0.029), a family member losing their job during the COVID pandemic (t=1.946, p=0.05), presence of non-productive cough (t=1.940, p=0.05), fatigue (t=2.418, p=0.017)), myalgia (t=2.015, p=0.046), having Diabetes Mellitus (t=2.151, p=0.033) and requiring oxygen therapy (t=2.030, p=0.040) were significant risk factors for higher anxiety scores. Conclusions: The feasibility of screening for depression and anxiety by non-mental health professionals in poorly technology-enabled moderately ill inpatient populations within LAMIC settings have been demonstrated. Psychosocial disadvantage and indicators of relatively severe covid infection seem to be risk factors for depression and anxiety. A system for screening for these disorders employing feasible strategies should ideally be incorporated to mitigate both short term and long-term negative consequences of this pandemic, particularly in inpatient populations, who are already subject to various vulnerabilities.